1990
DOI: 10.1021/tx00017a012
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic activation of 1,2-dibromo-3-chloropropane to mutagenic metabolites: detection and mechanism of formation of (Z)- and (E)-2-chloro-3-(bromomethyl) oxirane

Abstract: 1,2-Dibromo-3-chloropropane (DBCP), a haloalkane nematocide and soil fumigant, is metabolically activated to chemically reactive species that are direct-acting mutagens in a Salmonella typhimurium TA 100 test system. Studies in vitro with rat liver microsomes indicated that oxidation at carbon 3 resulted in the formation of an unstable gem-chlorohydrin that rearranged with elimination of hydrogen bromide to form (Z)-2-chloro-3-(bromomethyl)oxirane [(Z)-CBPO] and (E)-2-chloro-3-(bromomethyl)oxirane [(E)-CBPO]. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Mass spectral data of hexane-extracted reaction samples indicate that l-bromo-3-chloroacetone (BCA) is a major product of DBCP decomposition under oxygen-rich conditions. Figure 2 compares the electron impact mass spectrum to a mass spectrum obtained by Pearson et al (1990). Abundances at mass-to-charge ratios of 170,172, and 174 are rationalized as the parent molecular ion pattern.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mass spectral data of hexane-extracted reaction samples indicate that l-bromo-3-chloroacetone (BCA) is a major product of DBCP decomposition under oxygen-rich conditions. Figure 2 compares the electron impact mass spectrum to a mass spectrum obtained by Pearson et al (1990). Abundances at mass-to-charge ratios of 170,172, and 174 are rationalized as the parent molecular ion pattern.…”
Section: Resultsmentioning
confidence: 99%
“…The P-450, monooxygenase system oxidizes the carbon 2 position of DBCP, producing an unstable bromohydrin which spontaneously eliminates H + B r to form the BCA product. Omichinski et al (1988) and Pearson et al (1990) have also measured DBCP decomposition with whole-cell extracts containing liver microsomal P-450 enzyme. They found that, in an oxygen environment, the enzyme can hydroxylate each of the three carbons of 1,2-dibromo-3-chloropropane (DBCP) to yield a number of metabolites, including BCA if carbon 2 is hydroxylated.…”
Section: Resultsmentioning
confidence: 99%
“…A correlation between the bacterial mutagenicity of DBCP and P450-generated 2-bromoacrolein has been established (Omichinski et al, 1988b). Recently, formation of three additional electrophilic metabolites by P450 oxidation of DBCP was reported to contribute to the bacterial mutagenicity (Pearson et al, 1990a). It is possible that some or all of these metabolites may be involved in DBCP-induced DNA-damage, as well as tissue necrosis, in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, DBCP induces extensive DNA damage in several organs in vivo (Teramoto et al, 1980;Omichinski et al, 1987;SCderlund et al, 1988;Brunborg et al, 1990). DBCP may be activated by both P450 and glutathione (GSH) dependent pathways to reactive electrophilic species (Omichinski et al, 1987 andPearson et al, 1990a;.…”
Section: Introductionmentioning
confidence: 99%
“…Short-chain halogenated alkanes, which we utilized for the study of deguanylation of guanine based-nucleosides, have been widely used industrially as chemical intermediates, extraction solvents, degreasing compounds, copolymer cross-linking agents, or have been reported to be mutagenic and carcinogenic. [8][9][10][11][12][13][14][15][16][17] Among the sixteen different halogenated alkanes, we observed massive deguanylation of nucleosides by 2-bromo-2-methylpropane (2-B-2-MP), 2,3-dibromopropene (2,3-dBPe), 2-bromopropane (2-BP), bromoethane (BE) and 2-iodopropane (2-IP). …”
Section: Introductionmentioning
confidence: 99%